Tour guide and drone-based video tourism training to optimize the potential development of Kurau Village, Bangka - Agci Hikmawati; Maulana Arif; Dwi Indra Aprilliandari (Universitas Muhammadiyah Magelang, 2024)
The tourism sector is recognized as a pivotal industry capable of driving economic growth, particularly in regions abundant with tourism, cultural, and MSME potentials. Village officials and community members play crucial roles in fostering local economic development. However, the absence of English-speaking tour guides among village residents poses a significant challenge. This program aims to address this issue by supporting English-speaking tour guides to showcase local wisdom to international tourists. Additionally, the program seeks to enhance tour guides' skills in creating drone-based videos. Implementation involves training local tourism awareness groups to proficiently communicate in English and produce drone-based promotional videos of tourist destinations. The outcomes of these activities include improved English language proficiency among partners following tour guide training, as well as partners' ability to operate drones and produce promotional videos in accordance with established procedures. This initiative holds great significance for the Kurau Tourism Community group, particularly in enhancing English communication skills and creating tourism videos to bolster Kurau's tourism sector.